“Human factor” in the occupational health and safety: causes of the occurrence and ways to minimization - Bochkovskyi , Andrii; Sapozhnikova , Natalia; Nikolaiev , Dmytro; Savichevych , Olena (Social Development and Security, 2020)
The study found that during determining the causes of the occurrence and minimization of the manifestations of the “human factor”, it is advisable to study not individual personal causes that prompted a person to certain dangerous actions (inaction), but general causes inherent in a certain labor society. In order to study the causes of manifestations of the “human factor” and develop ways to minimize them, using a questionnaire survey, 1565 respondents – representatives of labor collectives of Odessa and Odessa region, divided by gender, age and professional characteristics – were interviewed. According to the survey, it is found that the main causes of occurrence the manifestations of the “human factor” are non-compliance with the requirements of occupational health and safety normative legal acts, violation of rules and regulations of instructings by the managers, deliberate violation of occupational health and safety instructions by employees, perfunctory testing employeesʼ knowledge of occupational health and safety, low level of social responsibility of managers and their lack of understanding of the economic benefits from improving the state of occupational health and safety at the enterprise. The main ways to minimization the manifestations of the “human factor” are identified; they are following necessary: the transition of the existing system of compulsory social insurance in Ukraine, which provides for the payment of a single social contribution by the employer, to a system of differential, risk-based approach to determining the size (for each company) of insurance rates, while introducing a system of tariff coefficients “bonus-malus”; reforming the system of higher and professional technical education, by returning the cycle of occupational health and safety disciplines to the status of normative with the establishment of unified, for all educational institutions with appropriate levels of accreditation, standard programs for studying these disciplines, which take into account areas of training (specialties) of future specialists; and also solving the problem of inconsistency of the specialty (professional education) of teachers of educational institutions with professional orientation of the cycle of disciplines of occupational health and safety; general popularization of occupational health and safety in society through information support at the state level, the concept of safe work, etc.